Envelhecer na cidade: memórias de mulheres aposentadas oriundas do espaço rural (Marechal Cândido Rondon - PR) - Hoerlle, Gladis (2013)
This work researches elderly women memory narratives that when young worked in agriculture and after retirement went to live in urban areas of Marechal Cândido Rondon, western Paraná. The mechanization of agriculture introduced in the 1970 s and other transformations in the production process in the field since then, led to deep changes in ways of living and working. Many of the settlers as aged and achieved the retirement, moved to urban areas, entrusting the property to the adult children s care, or in the case of owners of smaller lands, sold them to large producers to invest in another type of activity or living on their retirement. In this sense, through interviews of life stories, we analyze the experience of migration and rural-urban relationships that still exist, the strangeness and progressive adaptation to the city as well as the building of new relationships of belonging. Furthermore, we understand the changes in social roles and the sociability of these women, the empowerment acquired by retirement achievement and meanings they attribute to this process